Diseño de un sistema de aire acondicionado para la Procuraduría General de la Nación sede Judicial Ibagué (2020)
For the development of the project starts conducting an assessment of the conditions of air conditioning at the headquarters of the attorney general of the nation taking technical measurements of dry bulb temperature, wet bulb temperature and relative humidity, inside each offices two floors of the PGN. It is documented in written conditions of the system for installation where space is determined that requires climatizar, the number of people who work and frequent the venue, too, existing electrical and electronic equipment are characterized by the Attorney General is determined. documentary evaluation is performed on existing air conditioning systems on the market classifying them according to their physical layout and cooling method, to determine which system is adapted to the required conditions in the prosecutor's office.